2010
DOI: 10.1103/physreve.82.056408
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic study of plasma amplifiers for soft-x-ray lasers: A transition in hydrodynamic behavior for plasma columns with widths ranging from20μmto 2 mm

Abstract: Plasma-based seeded soft-x-ray lasers have the potential to generate high energy and highly coherent short pulse beams. Due to their high density, plasmas created by the interaction of an intense laser with a solid target should store the highest amount of energy density among all plasma amplifiers. Our previous numerical work with a two-dimensional (2D) adaptive mesh refinement hydrodynamic code demonstrated that careful tailoring of plasma shapes leads to a dramatic enhancement of both soft-x-ray laser outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 43 publications
0
22
0
3
Order By: Relevance
“…Oliva et al have shown [33] that a three-level model has good agreement with their experimental data. In their model, they took into account only Doppler broadening, while collisional broadening should also be treated.…”
Section: Pumping and Relaxation Timementioning
confidence: 68%
See 1 more Smart Citation
“…Oliva et al have shown [33] that a three-level model has good agreement with their experimental data. In their model, they took into account only Doppler broadening, while collisional broadening should also be treated.…”
Section: Pumping and Relaxation Timementioning
confidence: 68%
“…The populations of the Ne-like levels are computed in a three-level model [33,34]; Figure 1. Oliva et al have shown [33] that a three-level model has good agreement with their experimental data.…”
Section: Pumping and Relaxation Timementioning
confidence: 99%
“…The hydrodynamic parameters obtained from ARWEN were postprocessed [38,49] to obtain 2D maps of atomic data in the small-signal gain regime, and to determine the saturation fluence. This postprocessing was done with a simple three-level atomic model that computed the gain and saturation fluence on the 2p 5 1/2 3s 1/2 , J D 1 !…”
Section: Model To Obtain 2d Maps Of Atomic Datamentioning
confidence: 99%
“…The gain reached a maximum value of 61 per cm, to be compared with 60 per cm measured by Wang et al The surface of the gain zone is rather small (cf. [38,49]), due to a very strong plasma expansion along the target surface. This flow induces a fast drop of density and temperature, and thereby a reduction of the collisional pumping.…”
Section: Model To Obtain 2d Maps Of Atomic Datamentioning
confidence: 99%
“…When the focal width is larger than 100 µm, the gain zone is rather homogeneous. These changes are due to a reduction of the thermal losses by lateral conduction and radiation cooling as well as the inhibition of the lateral expansion when increasing the focal width [16]. Considering a 1 mm large plasma that may be created with a sub-PW laser, about 0.4 mJ is stored on the population inversion.…”
Section: Numerical Sectionmentioning
confidence: 99%